PERTUMBUHAN TANAMAN KANGKUNG (Ipomoea aquatica (L.) Forsk.) PADA TANAH GAMBUT DENGAN PENAMBAHAN CANGKANG TELUR, ABU SEKAM DAN PUPUK KANDANG - Nurul Makromah; Diah Rachmawati; Santosa Diah Rachmawati (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2011)
The applications of peat as a farm there are many limiting factors, among others, the reaction is very acidic soil and low nutrient content available. To overcome these problems usually done liming the soil. The addition of lime causes an increase in pH and nutrient  availability. This study used the eggshell and husk ash as a source of calcium to overcome the lack of calcium in the soil and to determine the effect of manure on the growth of kale. This study used 1.5 kg of peat per polybag and one plant per polybag. This study used a completely randomized design (CRD) factorial. The first factor eggshell  with four levels namely: 0,0-1,5-3,0 and 4.5 g per polybag then the second factor with four level husk ash  are: 0,0-5,0-10,0 - 15.0 g per polybag. The third factor of manures are: 0.0 and 50.0 g per polybag. Do six replicates of each treatment combination. Growth parameters were observed plant height, number of leaves, fresh weight of shoot and root, root shoot ratio, pH of peat soil, content of Ca and Fe in shoots. Data were analyzed by Anova and a further test using Duncan's Multiple Range Test (DMRT) at the test level α = 5%. The addition of manure increased plant growth of kale. The addition of egg shells raise the pH of peat soil. The addition of rice husk ash and manure on peat soil decreases the concentration of Ca and Fe on shoot of kale. Keywords: peat, kale, egg shells, rice husk ash, manure